2002
DOI: 10.1099/0022-1317-83-11-2845
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factors encoded by Orf virus show surprising sequence variation but have a conserved, functionally relevant structure

Abstract: The first report of a vascular endothelial growth factor (VEGF)-like gene in Orf virus included the surprising observation that the genes from two isolates (NZ2 and NZ7) shared only 41n1 % amino acid sequence identity. We have examined this sequence disparity by determining the VEGF gene sequence of 21 isolates of Orf virus derived from diverse sources. Most isolates carried NZ2-like VEGF genes but their predicted amino acid sequences varied by up to 30n8 % with an average amino acid identity between pairs of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
57
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 28 publications
(64 reference statements)
3
57
0
2
Order By: Relevance
“…It was demonstrated that all VEGFs of established PPV species (including PCPV VR634; Ueda et al, 2003) also possess the ability to induce endothelial proliferation and angiogenesis and are likely to be responsible for the highly vascularized and proliferative nature of PPV lesions (Savory et al, 2000;Wise et al, 2003;Inder et al, 2007;Ueda et al, 2003Ueda et al, , 2007. This is in spite of the fact that sequence variation of vVEGF proteins is remarkably high, varying from 35 to 63 % aa identity between species, whilst isolates of the same species show as little as 38 % aa sequence identity (Lyttle et al, 1994;Mercer et al, 2002Mercer et al, , 2006Wise et al, 2003Delhon Fig. 4.…”
Section: Hautaniemi and Othersmentioning
confidence: 65%
“…It was demonstrated that all VEGFs of established PPV species (including PCPV VR634; Ueda et al, 2003) also possess the ability to induce endothelial proliferation and angiogenesis and are likely to be responsible for the highly vascularized and proliferative nature of PPV lesions (Savory et al, 2000;Wise et al, 2003;Inder et al, 2007;Ueda et al, 2003Ueda et al, , 2007. This is in spite of the fact that sequence variation of vVEGF proteins is remarkably high, varying from 35 to 63 % aa identity between species, whilst isolates of the same species show as little as 38 % aa sequence identity (Lyttle et al, 1994;Mercer et al, 2002Mercer et al, , 2006Wise et al, 2003Delhon Fig. 4.…”
Section: Hautaniemi and Othersmentioning
confidence: 65%
“…All VEGF-A isoforms bind to VEGFR-1 and VEGFR-2, whereas PlGF and VEGF-B are specific for VEGFR-1. Furthermore, pox viruses encode VEGF variants collectively called VEGF-E that specifically bind to VEGFR-2 (23)(24)(25).…”
mentioning
confidence: 99%
“…4, A and B, shows the critical residues determining receptor binding of VEGF-A, PlGF, and VEGF-E NZ7. These residues presumably also regulate receptor interaction of VEGF-E NZ2, Vammin, and VR-1 (29,32,48). The three loop regions, L1 (magenta), L2 (slate), and L3 (orange), that determine the interaction with VEGFR-1 and -2 (48) are marked.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we made the mutant VE R46I by exchanging Arg 46 with the corresponding amino acid in VEGF-A, Ile. This mutant was constructed to assess the importance of the previously postulated salt bridge between Arg 46 and Glu 64 that was suggested to block binding of VEGF-E to VEGFR-1 (29). Dimer formation of VEGF-E NZ2 mutants was determined by SDS-PAGE under reducing and nonreducing conditions after the proteins were deglycosylated with endoglycosidase F (supplemental Fig.…”
Section: Receptor Binding Properties Of Vegf-e/plgf Chimericmentioning
confidence: 99%
See 1 more Smart Citation